Multicultural History Education and Character Formation: A Case Study at SMAN 1 Prambanan - Alfatikha Ainia Prihadi; Dyah Kumalasari; Amirul Syafiq; Fathurrahman Fathurrahman (AL-ISHLAH: Jurnal Pendidikan, 2025)
Indonesia’s cultural plurality presents ongoing challenges related to intolerance and disintegration. Schools must adopt multicultural educational strategies to cultivate character and harmony among students from diverse backgrounds. This study explores how multicultural-based history education supports character formation at SMAN 1 Prambanan. A qualitative case study approach was employed over three months (February–April 2024). Data were collected through observation, interviews, and document analysis. Participants included two history teachers and six students of varied religious and ethnic backgrounds, selected via purposive sampling. Triangulation ensured data credibility. The study found that the integration of multicultural values in history learning—through material selection, inclusive group assignments, and participatory discussions—fostered six core character traits: reverence for God, global diversity, cooperation, critical thinking, patriotism, and compassion. Teachers facilitated inclusive classroom dynamics and encouraged critical engagement with historical narratives. Students displayed tolerance and active participation across religious and ethnic differences. However, challenges included outdated teaching methods, limited instructional resources, and insufficient multicultural training for teachers. Multicultural history education can serve as an effective platform for character building in pluralistic settings. Teachers’ roles in modeling inclusive behavior and designing context-sensitive learning activities are pivotal. Institutional support for teacher training and digital resource integration is necessary to enhance implementation. Multicultural values embedded in history education at SMAN 1 Prambanan promote character formation and intergroup tolerance. This model has potential for broader application in similar educational contexts.